Glide Quality in Cross-Country Skiing : The Topographical and Frictional Impact of the Stone Grind - Johansson, Martin (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2022)
The Swedish Winter Olympic team is one of the strongest Olympic teams in theworld, and the majority of the team’s success comes from ski-related sports. So howcan the Swedish team remain, and maybe even accelerate, its competitive advantage? The answer is science. In order to narrow down the broad field that is equipment development, this thesishad the purpose to examine the stone grind’s impact on friction between the ski andthe snow. To achieve this purpose, the project was designed to answer these threequestions: • How does the ski base impact the friction between the ski and the snow? • How do the stone grind’s parameters impact the ski base? • How do the stone grind’s parameters impact the friction between the ski andthe snow? To answer these questions, a total of three pilot tests were done before the finalfull-scale experiment. The method to strategically test the parameters of the stonegrind was to use a full two-level factorial design, with a total of three stone grindparameters being investigated. Those parameters were: Cutting Depth, Line Density,and Wheel Pressure. The skis were tested in Arctic Fall’s indoor facilities where theskis were tested with a winch set-up to get the skis up to a desired speed, and thedata collected from the test were speed data from each of the skis. This speed datawould then be used to calculate the coefficient of friction acting between the ski andthe snow. To understand the stone grinds parameters on the ski base, the ski basesurfaces were measured after the skis were grounded, to build a regression modelconsisting of stone grind parameters as independent variables, and surface parametersbeing the dependent variables. A model was created suggesting that in the conditions the tests were executed, thesurface parameters Sa should be minimized and Sm should be maximized to achievea minimized coefficient of friction. A more generalisable model to impact the surfaceparameters Sa and Sm was also generated. It suggests that to impact Sa and Sm, itis the stone grind parameter ...